Dietary Supplementation of Eubiotic Fiber Based on Lignocellulose on Performance and Welfare of Gestating and Lactating Sows - Odakura, Agnês Markiy; Caldara, Fabiana Ribeiro; Burbarelli, Maria Fernanda de Castro; Almeida Paz, Ibiara Correia de Lima [UNESP]; Garcia, Rodrigo Garófallo; Oliveira dos Santos, Viviane Maria; de Brito Mandu, Daniella Ferreira; Braz, Jaqueline Murback; Lourenço da Silva, Marconi Italo [UNESP] (MDPI, 2023)
The present study aimed to evaluate the effects of partially fermentable insoluble dietary fiber supplementation on the behavior, surface temperature, and reproductive parameters of gestating and lactating sows, as well as on the performance of their litters. Four hundred hyper-prolific sows were assigned in a randomized block design with two treatment groups during the gestation phase: Control (C), corn-soy based diets, or corn-soy based diets with daily 55 g supplementation of eubiotic fiber (F) from the 85th day of gestation until the farrowing (late pregnancy). During the lactation phase, the sows were assigned in a 2 × 2 factorial design using the following treatment groups: (1) CC, no fiber included during gestation and lactation. (2) FC, daily inclusion of 55 g of fiber only during late pregnancy. (3) CF, daily inclusion of 55 g of fiber only during lactation. (4) FF, daily inclusion of 55 g of fiber during late pregnancy and lactation. Sows that received dietary fiber supplementation during the final third of gestation increased feed intake during lactation. Piglets from sows supplemented in both phases showed a significant increase in weight at weaning. The dietary supplementation of eubiotic fiber for sows in the end period of gestation and lactation improved performance and welfare, with positive consequences for developing their litters.
Keywords: behavior; infrared thermography; intestinal microbiota; reproductive performance; well-being